2018
DOI: 10.1007/s00277-018-3250-8
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells transplantation in hematological patients with acute graft-versus-host disease: characteristics and risk factors for infectious complications

Abstract: The role of MSCs in infection prevention and treatment is still discussed in transplant and hematological patients. The spectrum and risk factors for infections after MSCs transplantation in patients with acute GVHD have not been studied before. To determine the risk factors and spectrum of infectious complications in patients received mesenchymal stem cell transplantation as a treatment for acute GVHD. A prospective observational study was performed to evaluate the risk factors and characteristics of infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The therapeutic potential of MSCs has been explored in a number of phase I, II, and III clinical trials [23], of which several were targeted against graft versus-host disease and to support engraftment of hematopoietic stem cells [24, 25]. Yet, very few of these trials use MSCs to treat tumor diseases [23, 26, 27], such as gastrointestinal, lung, and ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The therapeutic potential of MSCs has been explored in a number of phase I, II, and III clinical trials [23], of which several were targeted against graft versus-host disease and to support engraftment of hematopoietic stem cells [24, 25]. Yet, very few of these trials use MSCs to treat tumor diseases [23, 26, 27], such as gastrointestinal, lung, and ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…They showed a trend towards clinical efficacy in patients with SR grade II–IV aGVHD, with a marginal six‐month OS difference between those receiving MSCs and the historical control group (58.82% vs 38.24%; p = 0.0678). In this relatively small study, no statistically significant risk of bacterial infections, cytomegalovirus (CMV) disease and invasive fungal disease was observed 72 . Cetin et al treated 17 patients with aGVHD; survival rate at six months was 69.2% in the responder group ( n = 13) compared with no survival in the non‐responder group ( n = 4) 73 .…”
Section: Mscs For the Treatment Of Gvhd And Haemorrhagic Cystitismentioning
confidence: 81%
“…We did not evaluate whether the infection rate had increased. Other studies have not reported an adverse effect that increased the rate of infection [12,26,27].…”
Section: Discussionmentioning
confidence: 99%